The neighbourhood home : An environments system from sharing to caring - Longo, Ilaria; Massari, Sonia; Spalletta, Alessandro (My University, 2021)
Cities are changing. Wars, climate change and idealised betterlife opportunities open the doorsformassive migration.Unfortunately, however,the new arrivalswith their different backgroundsand lifestylesare often perceived as a threat to pre-existing culture and home. But what is ‘home’?From the results of ethnographic researchand an online opensurveyconducted for amaster’s degreefinal thesis in systemic design, ‘home’ is the neighbourhoodthat involves all the values and behaviours that everyone needs in their everyday life. This research led to theacademic conceptof the ‘neighbourhood home’, a system of new environments for future inclusive cities that aims to make all the inhabitants ‘feel at home’.This notionis based on the ideathat inclusion isdeveloped throughempathy, creativity and know-how, discoveringthe culturalritualsand myths of different peoples. In every structure (like Homesof Music, Language, Clothing, etc.),new and old citizens can rediscover their common roots, whichhave always been, today as yesterday, interconnected through a multiplicity ofculturalhandicraftexpressions.The pilot projectdesigned is ‘MeetEat’, a home that promotes informal cooking classes andsocial eatingandis ingredient-driven (chosen on a seasonal basis) and organisedby volunteercitizens in the neighbourhood. With the neighbourhood home’thesis, we aim to propose a system that can turn diffidence into curiosity,conflicts into sharingandexclusioninto caring.
Keywords: City; Sharing; Roots; Inclusion; Migration